Comparative anatomical characters of the genus Aerides Lour. (Orchidaceae) in Thailand - WORACHAT TOKAEW; DUANGMANEE KRUBKRATOKE; SAOWALAK PAYAKDET; PHUTSADEE PHROMPRASIT (Society for Indonesian Biodiversity, 2023)
Abstract. Tokaew W, Krubkratoke D, Payakdet S, Phromprasit P. 2023. Comparative anatomical characters of the genus Aerides Lour. (Orchidaceae) in Thailand. Biodiversitas 24: 6641-6651. The genus Aerides Lour. belonging to the subfamily Epidendroideae (Orchidaceae), which are ornamental plants in Thailand. The identification of Thai Aerides is mostly based on the flower morphology which is a short period. The vegetative parts of Aerides species have similar characters. The anatomical data are also helpful for the identification of the Aerides species. Therefore, this study aimed to observe the vegetative stages (leaf and root) of seven species of Aerides in Thailand. Permanent slides of the leaf epidermis were prepared by epidermal peeling and stained with safranin. Transverse sections of leaf lamina and root were prepared using the paraffin method with a rotary microtome. They were then stained with safranin and fast green, examined using a light microscope, and their anatomical characteristics were described. The results showed that certain anatomical characteristics can be used for species identification, including distribution of stomata, presence of crystals, types of crystals, xylem arches in the root, shapes of the midrib and margin, and presence of starch grains. The key to species of Aerides species in Thailand based on anatomy characters is constructed. Anatomical features can be used for taxonomically important data and provide more information on the anatomical properties of Thai Aerides.